Occurrence of depression symptoms measured by the Beck Depression Inventory (BDI) in women after mastectomy and breast reconstruction with regard to the assessment of quality of life - Szadowska-Szlachetka, Zdzisława Cecyllia; Stanislawek, Andrzej; Kachaniuk, Hanna; Charzyńska-Gula, Marianna; Bartoszek, Agnieszka; Gałęziowska, Edyta; Domżał-Dzewicka, Renata; Kocka, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2013)
Introduction : More women with less advanced breast cancer have been recently offered tumorectomy, and, if mastectomy is necessary, most women can benefit from breast reconstruction, reimbursed by the National Health Fund. The aim of the study was to determine whether there are differences in the assessment of the depression intensification measured by the Beck Depression Inventory (BDI) among women after mastectomy and breast reconstruction in correlation with quality of life measured by EORTC QLQ-C30 and QLQ-BR23. Material and methods : The research covered a group of 241 women from oncology hospitals in Lublin. 55.19% (n = 133) were women after mastectomy, while 44.81% (n = 108) were women after breast reconstruction. During the research, the following questionnaires were used: EORTC QLQ-C30 – to assess the quality of life of cancer patients, QLQ-BR23 – to assess the quality of life of women with breast cancer, and a screening questionnaire to assess the risk of depression, i.e. BDI. Statistical analyses were conducted based on STATISTICA 8.0 Program, assuming a significance level of p < 0.05. Results : The research shows that breast reconstruction has a significant effect on the assessment of the quality of life of operated women and that, in this population, the depression symptoms measured by BDI occur less frequently. Conclusions: Because of higher intensification of depression in women after mastectomy, they assess the quality of life lower than women after breast reconstruction.